2023
DOI: 10.1007/s00467-023-06006-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of idiopathic nephrotic syndrome during the Covid-19 pandemic in the Paris area (France) and in the Netherlands

Abstract: Background The aetiology of idiopathic nephrotic syndrome (INS) remains partially unknown. Viral infections have been associated with INS onset. Since we observed fewer first onset INS cases during the Covid-19 pandemic, we hypothesised that lower INS incidence was the result of lockdown measures. Therefore, the aim of this study was to evaluate the incidence of childhood INS before and during the COVID-19 pandemic in two independent European INS cohorts. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…[39][40][41][42] Additionally, observational studies reported reductions in the incidence and relapse of the nephrotic and nephritic syndrome amongst children. 43,44 The reasons behind the decrease in glucosuria remain largely unknown; however, changes in adiposity status may not be attributed to this decrease because the incidence rate of diabetes mellitus amongst Japanese children is very low, at 2-3 cases per 100 000 person-years, 45 making it improbable to be reflected in the current data. Alternatively, an increase in the consumption of instant and processed foods during the COVID-19 pandemic might explain the reduction in glucosuria amongst children.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…[39][40][41][42] Additionally, observational studies reported reductions in the incidence and relapse of the nephrotic and nephritic syndrome amongst children. 43,44 The reasons behind the decrease in glucosuria remain largely unknown; however, changes in adiposity status may not be attributed to this decrease because the incidence rate of diabetes mellitus amongst Japanese children is very low, at 2-3 cases per 100 000 person-years, 45 making it improbable to be reflected in the current data. Alternatively, an increase in the consumption of instant and processed foods during the COVID-19 pandemic might explain the reduction in glucosuria amongst children.…”
Section: Discussionmentioning
confidence: 89%
“…Consequently, the incidence rates of most infectious diseases (e.g., group A streptococcal pharyngitis) substantially reduced during this period, suggesting decreased incidence of post‐infectious nephritis 39–42 . Additionally, observational studies reported reductions in the incidence and relapse of the nephrotic and nephritic syndrome amongst children 43,44 . The reasons behind the decrease in glucosuria remain largely unknown; however, changes in adiposity status may not be attributed to this decrease because the incidence rate of diabetes mellitus amongst Japanese children is very low, at 2–3 cases per 100 000 person‐years, 45 making it improbable to be reflected in the current data.…”
Section: Discussionmentioning
confidence: 99%